2018
DOI: 10.3390/ijerph15092040
|View full text |Cite
|
Sign up to set email alerts
|

The Measure of the Family Caregivers’ Experience

Abstract: Objective: Design and validate a measure of the experience of family caregivers with the integrated care that receive the persons they care for. Methods: The new instrument for measuring the experience of caregivers is based on the Instrument to Evaluate the EXperience of PAtients with Chronic Diseases (acronym in Spanish: IEXPAC) scale instrument. With the qualitative technique of the discussion group, nine professionals and eight caregivers assessed the face validity of the instrument and they advised on iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…We used the Japanese version of the Caregivers’ Experience Instrument (J-IEXPAC CAREGIVERS). The Caregivers’ Experience Instrument, also called IEXPAC CAREGIVERS, is a scale which measures family caregivers’ experience of integrated health and social care for both patients with chronic conditions and their family caregivers [ 25 ]. This scale was developed and validated in Spain, based on the Instrument to Evaluate the EXperience of PAtients with Chronic Diseases (acronym in Spanish: IEXPAC), which is theoretically based on the Chronic Care Model and is inspired by patient-centered integrated care approaches [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Japanese version of the Caregivers’ Experience Instrument (J-IEXPAC CAREGIVERS). The Caregivers’ Experience Instrument, also called IEXPAC CAREGIVERS, is a scale which measures family caregivers’ experience of integrated health and social care for both patients with chronic conditions and their family caregivers [ 25 ]. This scale was developed and validated in Spain, based on the Instrument to Evaluate the EXperience of PAtients with Chronic Diseases (acronym in Spanish: IEXPAC), which is theoretically based on the Chronic Care Model and is inspired by patient-centered integrated care approaches [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…We previously developed a Japanese version of a scale to measure family caregiver experience of interprofessional care for patients and families [ 24 ]. This instrument was originally developed in Spain to measure the quality of integrated health and social care [ 25 ], and includes elements of professional attention to the health and well-being of family caregivers themselves. This scale can be used to assess the quality of health and social care from the caregivers’ perspective.…”
Section: Introductionmentioning
confidence: 99%
“…(2) 100 103 (28.5%) 125 (34.5%) 129 (35.6%) 5 (1.4%) Q3 (3) 100 244 (67.4%) 81 (22.4%) (9.4%) 3 (0.8%) Q4 (4) 100 102 (28.2%) 168 (46.4%) 82 (22.7%) 10 (2.8%) Q5 (5) 100 138 (38.1%) 132 (36.5%) 49 (13.5%) 43 (11.9%) Q6 (5) 100 (4) 90.9 206 (62.6%) 107 (32.5%) 14 (4.3%) 2 (0.6%) Q9 (7) 99.7 259 (71.7%) 78 (21.6%) 18 (5%) 6 (1.7%) Q10 (4) 99.7 238 (65.9%) 94 (26%) 27 (7.5%) 2 (0.6%) Q11 (8) 100 45 (12.4%) 261 (72.1%) 56 (15.5%) Q12 (9) 100 29 (8%) 129 (35.6%) 140 (38.7%) 64 (17.7%) Q13 (5) 100 179 (49.4%) 134 (37%) 33 (9.1%) 16 (4.4%) Q14 (10) 100 26 (7.2%) 113 (31.2%) 204 (56.4%) 19 (5.2%) Q15 (7) 100 185 (51.1%) 133 (36.7%) 30 (8.3%) 14 (3.9%) Q16 (4) 100 167 (46.1%) 155 (42.8%) 32 (8.8%) 8 (2.2%) Q17 (4) 100 186 (51.4%) 142 (39.2%) 31 (8.6%) 3 (0.8%) Q18 (11) 100 253 (69.9%) 64 (17.7%) 21 (5.8%) 9 (2.5%) 14 (3.9%) 1 (0.3%) Q19 (12) 99.7 141 (39.1%) 117 (32.4%) 42 (11.6%) 29 (8%) 32 (8.9%) Q20 (5) 100 103 (28.5%) 133 (36.7%) 85 (23.5%) 41 (11.3%) D3. Social Services Q21 (13) 100 118 (32.6%) 244 (67.4%) Q22 (14) 32.6 58 (49.2%) 6 (5.1%) 46 (39%) 8 (6.8%) Q23 (15) 32.6 60 (50.8%) 28 (23.7%) 21 (17.8%) 1 (0.8%) 8 (6.8%) D4. Treatment Plan Q24 (16) 100 93 (25.7%) 181 (50%) 88 (24.3%) Q25 (4) 93 25.7 48 (51.6%) 40 (43%) 4 (4.3%) 1 (1.1%) Q26 (4) 93 25.7 35 (37.6%) 52 (55.9%) 6 (6.5%) Q27 (5) 48.1 51 (29.3%) 67 (38.5%) 10 (5.7%) 46 (26.4%) Q28 (4) 99.4 187 (51.9%) 104 (28.9%) 36 (10%) 33 (9.2%) Table 2.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Instruments such as the one developed by Nuño-Solinís et al [9] have shown very good ease-of-use in daily practice, but its application is limited to the organizational level. We need new instruments to measure care coordination across all levels of care, principally when registering the perspectives of the populations [14]. Through this approach, we aim to measure the impact on the health of the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation